A technique for enhancing learning about the professional practice of food microbiology and its preliminary evaluation - Dykes, Gary (2008)
Purpose - The purpose of this paper is to develop and preliminarily evaluate an exercise to enhance student learning and engagement about the professional practice of food microbiology. Design/methodology/approach - An exercise in the form of group problem-based investigations framed from the perspective of different stakeholders, namely food producers, regulator, consumer or mass media, was developed. Problems were designed to include some anomalies and errors that could be exploited by the students. Students presented their findings, which were peer reviewed and contributed to the summative assessment of the course. A preliminary investigation into the effectiveness of the exercise in engaging students and achieving learning outcomes was conducted using a questionnaire and responses to an examination question on the subject. Findings - Results from the preliminary evaluation questionnaire indicated that students were engaged by the exercise but some issues with group interactions were apparent. Students felt that they learned from the exercise but did not necessarily like it due to interpersonal problems within their groups. The learning outcomes were achieved with a number of students answering the examination question and indicating a deeper understanding of the issues related to microbiological food safety. Practical implications - The exercise described represents a way for integrating theory and practice in food microbiology where direct immersion in a professional situation may not be possible. Originality/value - Enhanced student learning about professional practice of the type described here could result in better "industry ready" graduates of the type required by employers. © Emerald Group Publishing Limited.